Ensuring Psychological Safety to Develop Students’ Risk-Based Thinking of the Specialty "Civil Security" - Yevtushenko Nataliіa; Tverdokhliebova, Natalia; Mezentseva, Iryna (Educational Challenges, 2022)
Ukrainian society is exposed to external threats from the war with Russia, which negatively affects the plans, goals and quality of life, increases psychological tension and leads to a deterioration in the mental and social health of the population. This also applies to participants in the educational environment. The relevance of studying the state, experience, psychological and social capabilities of modern students is growing during the conduct of hostilities in Ukraine. Hence, the issue of psychological safety in the interaction of participants in the educational environment in distance and mixed forms of education becomes a priority. The process of forming risk-oriented thinking of students of a technical educational institution provides for training in understanding the phenomenon of risk-based thinking in the unity of three incarnations: a person himself determines what is acceptable for him, taking into account possible negative consequences, the presence of moral attitudes to preserve the life and health of people of social values of development social relations that exclude danger. The purpose of this article is to study the features of ensuring psychological security in conditions of uncertainty during the war in order to form risk-oriented thinking of students of higher educational institutions of a technical profile. The methodology on which this article relies includes empirical methods (observation, conversation, dialogue) that are used in full-time and distance learning, and theoretical methods (analysis, synthesis, generalization, explanation, classification). Based on them, we formulate practical recommendations for providing psychological safety measures for the effective formation of risk-oriented thinking of students in modern learning conditions. Within the framework of our study, the following results were achieved: the stages of educational and educational work in the educational process, pedagogical techniques through which the formation of risk-oriented thinking among students takes place; the conditions under which the psychological security of the student’s personality will be ensured are formulated, the indicators of the success of the strategies for the psychological security of students of higher educational institutions in war conditions are identified. The article presents the concept of risk-based thinking of students, which provides for the ability to prevent actions to eliminate potential inconsistencies in technosphere safety, analyze all identified inconsistencies, and also take actions to prevent the recurrence of risk. The conclusions allow us to state that for the development of risk-oriented thinking, personal potential and abilities, it is important for a person to be in a safe and stable environment. A safe environment around the personality is the most important condition for its development. The Institute of Education is a psychological and pedagogical environment where specially organized conditions are developed for the development of a personality, included in the spatial, subject and social environment, the essence of which is a set of communicative actions and relationships between participants in the educational process.